Barriers and drivers of near-term climate change mitigation: a Canadian case study - Jeffrey Sauer; I Daniel Posen; Shoshanna Saxe (Environmental Research: Infrastructure and Sustainability)
This work investigates, through semi-structured interviews, the prospects for rapid transitions towards low-carbon civil infrastructure systems. Rapid greenhouse gas (GHG) mitigation is critical to facilitate the near-term (i.e. within five years) reductions needed to limit global temperature rise to 2 °C. In addition, ongoing delays in climate action in many countries and sectors mean that rapid interventions will be needed in the 2030s and 2040s as climate change evolves and the need to mitigate becomes more urgent. This work examines, among twenty decisionmakers involved in developing, operating, or using Canadian infrastructure: (1) ongoing and expected near-term GHG mitigation actions (2) barriers constraining faster change, and (3) mitigation goals and expectations of the near future. Interviews were coded to identify common perspectives. Results indicate that organizations prioritize enabling deep change in a more distant future over executing rapid change, that detailed roadmaps for meeting near-term (e.g. 2030) goals were rare, and that participants view government policy certainty as crucial to near-term action. This work identifies deficits in action on the near-term scale and aids policymakers and decisionmakers by describing planned near-term mitigation actions and assessing barriers to going faster.